Efektifitas promosi kesehatan melalui media audiovisual mengenai hiv/aids terhadap peningkatan pengetahuan remaja Tentang hiv/aids - Desi Natalia Nadek; Agrina - -; Misrawati - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was to determined the effectiveness of health promotion by audiovisual about HIV/AIDS for increasing knowledge adolescents about HIV/AIDS. The design of this research was Quasy experiment designed by Pre-posttest with control group were divided into experiment group and control group. The research was conducted on girl’s in the “SMA Tri Bhakti Pekanbaru”. The total sample were 80 people who were taken by using systematic random sampling techniques by noticing to the inclusion criteria. Measuring instruments that used in both groups were questionnaires that have been tested for validity and realibility. Analysis was used univariate and Wilxocon and Mann Whitney test using to bivariate analyzes. The results showed there was a significant increasing in the rate of change in knowledge adolescents about HIV/AIDS in experimental group has given health promotion about HIV/AIDS with p value (0.000) < α (0,05). It means that health promotion about HIV/AIDS was effective for improving knowledge adolescents about HIV/AIDS. The results of this research was recommend to every health care have to giving health promotion about HIV/AIDS by audiovisual to increasing knowledge about HIV/AIDS. Key words : Audio visual, HIV/AIDS, knowledge, health promotion